The residence plot selection model for family house in Vilnius by neutrosophic WASPAS method - Baušys, Romualdas; Juodagalvienė, Birutė; Žiūrienė, Rytė; Pankrašovaitė, Ina; Kamarauskas, Juozas; Usovaitė, Ana; Gaižauskas, Dovydas (International Journal of Strategic Property Management, 2020)
Good quality dwelling and the environment are related to the values of citizens’ existence. It can be highlighted as important questions in creating a sustainable living environment. The research and analysis carried out so far include global planning of the plot of a particular country or city according to economic aspects. Meanwhile, our model, which covers the key social aspects of choosing a residential house, will fill this gap. We propose an original problem formulated which includes the planning of the plot of a particular city according to economic, environmental and social aspects. Our work aims to investigate the criteria for the selection of single-family houses and to develop a theoretical evaluation model based on decision-making methods. The presented study deals with the problem of selecting a one-family house plot using the Weighted Aggregate Sum Product Assessment Methods (WASPAS) and the Step-Wise Weight Assessment Ratio Analysis Method (SWARA). During the research, parameters related to plot selection were evaluated: infrastructure, distance, cost, privacy, security and aesthetic view.First published online 17 March 2020